Clinical characteristics of intussusception secondary to pathologic lead points in children: a single-center experience with 65 cases - Lin, Xiao-kun; Xia, Qiong-zhang; Huang, Xiao-zhong; Han, Yi-jiang; He, Guo-rong; Zheng, Na (Pediatric surgery international, 2017)
Objective Intussusception secondary to pathologic lead points (PLPs) is a challenging condition for pediatric surgeons, and few studies have been published on this subject. The aim of this study was to review and analyze clinical data on the diagnosis and management of intussusception secondary to PLPs in children. Methods Between 2002 and 2016, a total of 65 pediatric patients with a diagnosis of intussusception secondary to PLPs were retrospectively reviewed. Results The series comprised 47 males and 18 females. The average age of the patients was 4.9 years old. All patients had typical clinical manifestations, and intussusception was proven by ultrasound. Fifty-one patients had recurrent intussusception, of whom 21 had one, 14 had two, 10 had three, and 6 had more than three. There were 20 episodes of recurrence within 24 h (39.2%), 15 episodes were found between 24 and 72 h (29.4%), and the remaining 31.4% (16/51) of recurrences occurred after 72 h. All patients received surgical intussusception reduction. Meanwhile, enterectomy was the procedure of choice in 55 patients, polypectomy in 5 patients, and cystectomy in 3 patients. The types of intussusception secondary to PLPs included small intestinal ( n = 25), ileocolic ( n = 19), ileocecal ( n = 11), ileo–ileocolic ( n = 9) and cecalcolic ( n = 1). The types of PLPs included Meckel diverticulum ( n = 32), intestinal duplication ( n = 14), benign polyps ( n = 5), malignant lymphoma ( n = 4), Peutz–Jeghers syndrome ( n = 3), mesenteric cyst ( n = 3), intestinal wall hematoma of hemophilia ( n = 2), allergic purpura ( n = 1), and hamartoma ( n = 1). All patients recovered well with no relapse during follow-up, except for one patient who had an intestinal obstruction from adhesions that occurred approximately 3 months after discharge and who was curable after conservative treatment. Conclusions Intussusception secondary to PLPs tends to exhibit recurrence. There are various types of intussusception secondary to PLPs. It is necessary to improve auxiliary examinations to identify the etiology and avoid intraoperative omission. Surgical reduction of intussusception secondary to PLPs is the preferred clinical management.